Working conditions at the workplaces of the charge sections of foundries - A. M. Lazarenkov; M. A. Sadokha (Литьë и металлургия)
The working conditions at the workplaces of foundry workers when performing work on the charge sites, production factors determining them are considered. The results of studies of the parameters of the working conditions of the considered professions of foundry workers in comparison with the standard values are presented. It is established that in a comprehensive assessment of the working conditions of workers at the charge sections of foundries, it is necessary to take into account the duration of stay at the working equipment, the equipment and hand tools used, the type of alloy being smelted (steel, cast iron, non‑ferrous metals) and the nature of production.